2018
DOI: 10.1002/admi.201800981
|View full text |Cite
|
Sign up to set email alerts
|

3D Assembly of Metal Nanoparticles at Oleic Acid/Water Interface via Their Autonomous and Rapid Interfacial Locomotion

Abstract: The assembly of colloidal metal nanoparticles at immiscible liquid interface has attracted considerable attention because of both enhanced physical properties associated with the assembly and controlled mass transfer at the interface for many sensing and catalytic applications. However, rapid production of 3D assembly of metal nanoparticles at liquid interface is still challenging. Here a facile and robust method is proposed to generate 3D assembly of colloidal metal nanoparticles at oleic acid/water interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In all cases, two Raman transitions for 2-NT are observed at 1076 and 1381 cm −1 corresponding to C−H bending and ring stretching, respectively (Figure 4b). 28 To quantitatively compare the signal enhancements of the substrates, we analyzed the peak areas for both Raman transitions (Figure 4c). The peak areas measured from AuNRon-Si wafer (i) and AuNR with site-selectively grown SiO 2 -on-Si wafer (iii) are similar to each other.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, two Raman transitions for 2-NT are observed at 1076 and 1381 cm −1 corresponding to C−H bending and ring stretching, respectively (Figure 4b). 28 To quantitatively compare the signal enhancements of the substrates, we analyzed the peak areas for both Raman transitions (Figure 4c). The peak areas measured from AuNRon-Si wafer (i) and AuNR with site-selectively grown SiO 2 -on-Si wafer (iii) are similar to each other.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The substrates are immersed in an ethanolic solution, in which 2-NT is dissolved and subsequently washed for the Raman scattering measurements. In all cases, two Raman transitions for 2-NT are observed at 1076 and 1381 cm –1 corresponding to C–H bending and ring stretching, respectively (Figure b) . To quantitatively compare the signal enhancements of the substrates, we analyzed the peak areas for both Raman transitions (Figure c).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Organic semiconductors are the most adapted active materials for OECTs because their performance to transport charge and host ions can be designed at will by molecular structure. OECTs are ideally suited for biological interfacing because of their stability in aqueous electrolytes, cytocompatibility, facile biofunctionalization, and sterilization by autoclaving . OECTs have evidently been used in logic circuits, some also integrating OFETs .…”
Section: Charge and Ion Transportmentioning
confidence: 99%
“…Moreover, since the chemical composition of the oil is unimportant, as long as it provides a high energy interface with water for self-assembly, a variety of organic solvents can be used as the oil phase, which provides an extremely versatile SERS platform, especially for studying dipolar analyte molecules with low solubility in water. [69][70][71][72][73][74][75] For example, Liu et al showed that six edible oils can be distinguished using SERS and interfacial 2D Au nanoparticle arrays as enhancing substrates (Figure 6c). [72] Moreover, they showed that oxidation and adulteration of the edible oils could also be detected with the assistance of principle component analysis.…”
Section: Section 15 Sers Applications Of 2d Nanoparticle Arrays At Wmentioning
confidence: 99%